Astrology as a Means of Dissemination of Buddhism - พลายนาค, อชิรพจณิชา (Journal of Buddhist Studies Chulalongkorn University, 2019)
Stories concerning astrology have made multiple appearances in Theravada Buddhist scriptures, and the course of stars that influence human lives has been studied during the time of the Lord Buddha. This shows that Buddhism acknowledges astrology as a branch of knowledge. However, Buddhism regards Buddhist monks’ involvement in astrology as inappropriate, as the Lord Buddha clearly prohibited them from doing so because it is not fitting for an ascetic life. The study finds that Buddhist monks are able to use astrology to alleviate people’s suffering, but that they should only use it as a persuasive tool, not as the main objective. Although doing so may be in conflict with Buddhist Teachings, its contribution to the happiness of society and a large number of people has led some Buddhist monks to allow it in order to persuade lay people who form the majority of society to have the right understanding of Buddhist doctrines so that they will protect and maintain Buddhism.